Chuck Palahniuckas Fight Club Apropos of Sartreas Bad Faith and Camusas Calculated (Global Journal of Human-Social Science, 2014)
This essay titled "Chuck Palahniuck's Fight Club Apropos of Sartre's Bad Faith and Camus's Calculated Culpability" explores the existential philosophy that exists in Chuck Palahniuck's first novel, Fight Club (1996). Surprisingly, there has been little discussion of this novel's connection to Jean-Paul Sartre's notion of the look and the three patterns of bad faith in Being and Nothingness nor of Camus's discussion of calculated culpability in The Just Assassins ; this has largely been overlooked and presents a creative opportunity to better interpret Fight Club , its concomitant existential analysis, and the continuing fight between Camus and Sartre's political stances, not to mention the interpretive territory of existentialist humor